DISINFECTION CAPACITY OF MOUTHWASHES USING AS ADMIX SOLUTION OF ALGINATE IMPRESSION: KAPASITAS DISINFEKSI OBAT KUMUR DENGAN MENGGUNAKAN SOLUSI CAMPURAN DARI CETAKAN ALGINAT - Sastrodihardjo, Sumadhi; Harahap, Kholidina Imanda (Dentika: Dental Journal, 2016)
Immersion and spraying with disinfectant solution are the effective disinfection methods for alginate impression. However these methods causes dimensional changes on impression. Therefore mouthwash, which also has disinfectant function on microorganism can be used as mixing solution for alginate impression material. The aim of this study is to analyze antibacterial capacity of mouthwashes that used as admix solution for alginate impression. Samples was made from alginate impression material in tablet form with 15 mm diameter and 1 mm thickness. Total samples are 35 , 5 for admix with aquadest as control, chlorhexidine 0.1%, povidon iodine, sodium fluoride 0.1% wv, respectively. Samples were put on incubated Staphylococcus aureus in petri dish and kept in incubator for 24 hours at 37°C. Immersion was performed by dipping 15 samples of hygedent admix with aquadest into mouthwash liquids for 15 minutes. Inhibition zone was measured by using digital calliper. Statistic analysis was performed by using ANOVA one way and unpaired t-test. The admix with chlorhexidine 0.1% show the inhibition zone by 8.09 mm, povidon iodine 0.52 mm, and sodium fluoride 0.1% wv 2.91 mm. By using immersion method they show 7.63 mm inhibition zone for chlorhexidine 0.1%, 1.51 mm for povidon iodine, and 0.91 mm for sodium fluoride 0.1% wv. There are insignificant differences between admix and immerse with chlorhexidine 0.1% solution (p= 0.25). It can be concluded that chlorhexidine mouthwash 0.1% has the equal antibacterial capacity when used for admix solution nor immerse the alginate impression.